Brief Notes: The Effect of Manufacturing Errors on the Stiffness of Rolling Contact Bearings - Stolarski, T.A. (Engineering Transactions, 1992)
The paper presents an analysis of the effect of manufacturing errors on the stiffness of rolling contact bearings. The analysis is confined to considerations of the unevenness of raceways and the variable dimensions and variable elasticity of rolling elements. Unevenness of the rollers in roller bearings can also be easily incorporated into the analysis.